Satisfacción sexual y autoestima en la persona adulta mayor - Ramírez-Elizondo, Noé (Universidad de Sonora, 2019)
The aim of this article is to analyze the importance of sexuality and self-esteem in the elderly. The information was collected through Scielo bases and EBSCO host data, as well as books and theses concerning the subject. Depending on the content found it should be noted that sexual satisfaction not only covers aspects coital but incorporates many others. It is also important to mention that sexual satisfaction affects the quality of life of older people and involves issues like self-esteem, so understanding this phenomenon can lead to improved quality of care provided health professionals to that population. It determined that sexual satisfaction is an influential element positively on the self-esteem of the elderly and thus is an improvement in their quality of life; also it concludes that sexual satisfaction in later stages of life should be a subject addressed by the nursing professionals because of the great benefits it can bring to the Alarm time provide comprehensive care in this population group.